Multimode Synchronization of Chaotic Semiconductor Ring Laser and its Potential in Chaos Communication - Kang, Zexin; Sun, Jiang; Ma, Lin; Qi, Yanhui; Jian, Shuisheng (IEEE journal of quantum electronics, 2014)
We investigate numerically the synchronization of two multimode semiconductor ring lasers (SRLs) and demonstrate its potential in chaos-based communication. The extent of the SRL's chaos regime under external optical feedback is evaluated in terms of bifurcation diagram and the optimal feedback strength range for reliable chaotic communication is discussed as well. Under proper conditions, the receiver SRL can be satisfactorily synchronized with the transmitter SRL due to the injection-locking effect. The message encoding and decoding using chaos shift keying technique have been analyzed from the point of view of the total lasing output. The possibility of recovering the message using unidirectional output (clockwise output or counterclockwise output) is also examined and compared with that of the total output. The tolerance of the proposed scheme to the SRL's fabrication limitation and parameter mismatch are studied. In view of these results, chaos-based synchronization and communication over fiber optical link, with or without the amplified spontaneous emission noise induced by amplification, are demonstrated. We also check the negative influence of fiber nonlinearity on the system transmission performance.